Proposta de banco de dados a partir do mapeamento da estrutura logística da região metropolitana de São Paulo - Zabotto, Bianca Caroline Nascimento (Universidade Federal de São Carlos, 2022)
The present work has as its objective the implementation of a database, with the purpose of making available a tool for the stakeholders, involved in urban logistics, to analyze the factors that affect cargo transportation. Considering the growing development of urban centers, it is possible to highlight five important factors that directly affect logistics operations, namely: regulatory measures; logistics problems; collaboration in the delivery of goods; environmental aspects; and risks. Different stakeholders act in different ways in urban logistics in large cities, where communication and interaction in the processes converge to results that are more efficient. The database implementation is divided into four stages: requirements analysis, which synthesizes the main information that will direct the database structure; the conceptual model, where the Entity-Relationship Diagram is implemented; the logical model, which is the definition of the database in a database management system; and finally, the physical model, where we explore the database through queries and reports. The database was developed for the Metropolitan Region of São Paulo, with the intention of facilitating the understanding of all involved when it comes to logistics operations.
Database proposal for mapping the logistics structure of the metropolitan region of São Paulo
Keywords: Banco de dados; Transporte urbano de carga; Logística; Database; Urban freight transport; Logistic; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES